Treatment as long-term prevention: sustained reduction in HIV sexual transmission risk with use of antiretroviral therapy in rural Uganda - Siedner, Mark J.; Musinguzi, Nicholas; Tsai, Alexander C.; Muzoora, Conrad; Kembabazi, Annet; Weiser, Sheri D.; Bennett, John; Hunt, Peter W.; Martin, Jeffrey N.; Haberer, Jessica E.; Bangsberg, David R. (AIDS (London, England), 2014)
Suppressive antiretroviral therapy (ART) substantially decreases HIV transmission in clinical research settings. We sought to measure the frequency and correlates of periods of transmission risk among individuals taking ART during multiple years of observation in rural, southwestern Uganda. Observational cohort study. We collected sexual behavior and viral load data in a Ugandan cohort of people living with HIV/AIDS from the time of ART initiation. We defined each 90-day visit as a potential transmission period if HIV-1 RNA was more than 400 copies/ml and the participant reported sexual transmission risk behavior, defined as unprotected sexual contact with at least 1 HIV-uninfected partners or partners of unknown serostatus in the prior 90 days. Results: We evaluated data from 463 individuals on ART over a median 3.5 years of observation and 5293 total study visits. During that time, over half (259, 56%) had detectable viremia or reported sexual transmission risk behavior at least once. However, only 23 (5%) had both simultaneously, at 28 (<1%) of all visits. Transmission sexual behavior was reported at 6% of visits with detectable viremia. In multivariable regression modeling, correlates of transmission risk periods included younger age, lower CD4þ cell count, low household asset ownership and increased internalized stigma. Although detectable viremia and/or sexual transmission risk behavior occurred in over half of individuals, ART reduced periods of HIV transmission risk by over 90% during up to 6 years of observation time. These findings provide further support for provision of ART, along with interventions to promote long-term adherence, to reduce HIV transmission in HIV-endemic settings.
Keywords: Antiretroviral therapy; HIV/AIDS; Sub-Saharan Africa; Treatment as prevention; Uganda